Selective biodegradation of dibenzothiophene and alkyl dibenzothiophenes in crude oils from the Linpan oilfield, Bohai Bay basin, eastern China - Shi, Shengbao; Chen, Jianfa; Zhu, Lei; Wang, Tieguan (Journal of Asian Earth Sciences: X, 2022)
•The number of alkyl substituents slowed the biodegradation of DBT homologs.•Selective biodegradation occurred in isomers of alkyl DBTs, especially in C2- and C3-DBTs.•The sulfur-shielded isomers are more susceptible to biodegradation than the sulfur-exposed isomers in C2- and C3-DBTs. The biodegradation of dibenzothiophene (DBT) and alkyl dibenzothiophenes (DBTs) were studied in crude oils from the Linpan oilfield, Bohai Bay basin, eastern China. The crude oils selected from the oilfield had been subjected to different degrees of biodegradation, i.e., non-biodegraded to severely biodegraded. With increasing biodegradation extent, the concentration of total DBTs in the crude oils rises from non- to heavily-biodegraded degrees, and then declines from heavily to severely-biodegraded degrees meanwhile the paraffins in the crude oils have been thoroughly removed. The differences in biodegradation rates had been observed between the homologues of alkyl DBTs, and the susceptibility to biodegradation of these homologues declines with increasing of the alkyl substituent number. Selective biodegradation occurred due to differences of carbon positions of alkyl substituents on molecular structure of DBTs. The sulfur-shielded isomers, such as 4,6-dimethyldibenzothiophene and 4-ethyl-6-methyldibenzothiophene, were more susceptible to biodegradation than the sulfur-exposed isomers, for example 2,8-dimethyldibenzothiophene and 1,2,7-+1,2,8-trimethyldibenzothiophenes (co-eluted as one peak in mass chromatograms). However, selective biodegradation of C4-DBTs isomers was less remarkable than the isomers of C2- and C3-DBTs, which reflected the complex processes of biodegradation.